Multidimensional Analysis of the Teaching Process of the Critical Thinking Skills - Seyat Polat (Research in Social Sciences and Technology, 2020)
This study aims to evaluate critical thinking skills in a multidimensional way. Based on this objective, the level of teachers’ critical thinking skills, how they conceptualize critical thinking, their practices of critical thinking in the classroom, and if the critical thinking is referred enough in the curriculum are analyzed in this research. In terms of the research objective, this study is mixed-method: The relational model was used for the quantitative part of the research, and the case study method was used for the qualitative part. The research data was collected in the academic year 2013-2014. The study group from which quantitative data was collected consists of 323 males and 377 females, totaling 700 teachers, and the other study group from which the qualitative data was collected involves 16 teachers working at two primary and two elementary schools.